Lazismu and Muhammadiyah Philanthropy in the Covid-19 Pandemic (CIPP Evaluation Model) - Suryadin, Asyraf; Nurfitriani, Nurfitriani; Sari, Winda Purnama (SCAD Independent, 2022)
The COVID-19 pandemic has had an impact on all fields, including education. LAZISMU has a big responsibility to help communities affected by Covid-19, especially students in Belitung, through the foster parent program to help orphans and students from underprivileged families. This study aims to evaluate the implementation of the Philanthropy program of the LAZISMU foster parents movement in the Belitung Regency. The method used was to use program evaluation with the CIPP evaluation model. This study indicated that the program has been running well but still needs to be improved so that the program's performance is more optimal. Assistance in tuition fees has been distributed appropriately according to the background in the form of programs. However, many other needs still need attention, especially during the Covid-19 pandemic. Overall the implementation of the program has been going well but needs to be improved.